Quinolinate Phosphoribosyltransferase Promotes Invasiveness of Breast Cancer Through Myosin Light Chain Phosphorylation - Liu, Chien-Liang; Cheng, Shih-Ping; Chen, Ming-Jen; Lin, Chi-Hsin; Chen, Shan-Na; Kuo, Yi-Hue; Chang, Yuan-Ching (Frontiers in Endocrinology, 2021)
Perturbed Nicotinamide adenine dinucleotide (NAD+) homeostasis is involved in cancer progression and metastasis. Quinolinate phosphoribosyltransferase (QPRT) is the rate-limiting enzyme in the kynurenine pathway participating in NAD+ generation. In this study, we revealed that QPRT expression was upregulated in invasive breast cancer and spontaneous mammary tumors from MMTV-PyVT transgenic mice. Knockdown of QPRT expression inhibited breast cancer cell migration, invasion, and tumorigenic potential in nude mice. Consistently, ectopic expression of QPRT promoted cell migration and invasion in breast cancer cells. Treatment with QPRT inhibitor (phthalic acid) or P2Y11 antagonist (NF340) could reverse the QPRT-induced invasiveness and phosphorylation of myosin light chain. Similar reversibility could be observed following treatment with Rho inhibitor (Y16), ROCK inhibitor (Y27632), PLC inhibitor (U73122), or MLCK inhibitor (ML7). Altogether, these results indicate that QPRT enhanced breast cancer invasiveness probably through purinergic signaling and might be a potential prognostic indicator and therapeutic target in breast cancer.